Biodiversity of Coreoidea and Pentatomidae (Heteroptera) from Atlantic forest protected areas : Insights into their conservation - Dellapé, Gimena (2018)
Although the majority of threatened species are likely to be tropical insects, knowledge of the diversity, ecological role and impact of insect biodiversity loss on ecosystem processes is very limited. Specimens belonging to four families of Heteroptera: Pentatomidae, Coreidae, Alydidae and Rhopalidae, were collected from a protected area in the Paraná Forest, the largest ecoregion of the Atlantic Forest, in Argentina. The assemblages were characterized and the biodiversity estimated, and they were compared with the assemblages found in five other protected areas in the Brazilian Atlantic Forest. In our study area, Pentatomidae had the greatest richness and diversity; Coreidae was the second most diverse family, with highest sampling deficit, highest percentage of singletons, and lowest inventory completeness; and Rhopalidae was the best sampled family with asymptotic rarefaction curves. We explored the application of the Species Conservation Importance index, following four criteria, to evaluate the relative importance of the pentatomid species studied and its usefulness for assigning conservation values to areas. We found similar Site Conservation Values among the six areas and noted that the use of criteria was limited by the lack of information, being crucial to increase the knowledge of most of the species.